Konsep Mencari Ilmu Bermanfaat Perspektif Kitab Ta’lim Muta’alim Karya Syekh Burhanuddin Ibrahim Az-Zarnuji - Hisyam, Azmi; Johan Idrus Tofaynudin (PAI RAFAH, 2024)
When a Muslim dies, he will not take his wealth to the grave, all his deeds will be cut off except for three things, namely sadaqah jariyah, prayers for righteous children, and useful knowledge. Knowledge that provides benefits is knowledge that makes a Muslim know his duties, functions and roles on earth. So, he gets closer and loves Allah SWT, not only world affairs, useful knowledge must also include religious affairs and everything related to it, and enter (dwell) in the recesses of the human heart, then give birth to feelings of calm, fear, surrender, humble himself and admit his weakness before Allah SWT. The virtue of people who study is that their reward will be carried until they die. To obtain valid research results, it is necessary to select sources, both primary data sources and secondary data sources. The primary data source of this research is the book “Ta`lim Muta`alim” by Imam Az-Zarnuji. While secondary data sources are scientific works. The concept of useful knowledge according to the perspective of the Book of Ta'lim Muta'allim by Imam Az-Zarnuji which contains recommendations for someone (tholib) who demands knowledge must have the intention of seeking knowledge, choosing knowledge, teachers and friends, honoring knowledge and scholars, sincerity, keistiqomahan and enthusiasm, learning strategies, tawakkal and wara' guarding themselves from bad deeds.